Management of synovial chondromatosis of the hip by open arthrotomy debridement only VS total hip replacement: A case report. (2020) - Prabowo, Yogi; Saleh, Ifran; Pitarini, Astuti; Junaidi, Muhammad Ade
Highlights: Both arthrotomy debridement only or followed by total hip replacement could be an option in treating synovial chondromatosis of the hip. Both treatment option shows a successful outcome by HHS and LEFS questionnaires without any recurrence marks. Grade of osteoarthritis and patient age can be a distinguish factor for choosing a treatment option. Abstract: Introduction: Synovial chondromatosis is an unusual nonneoplastic condition of joints. Clinical symptoms usually insidious, and the patient often came in the late stage of the disease. Treatment generally include arthroscopy debridement, open arthrotomy debridement to evacuate loose bodies, or in a very late stage with a collapsing joint, it might need a joint replacement arthroplasty. Methods: We report two cases of a 55-year old and a 22-year-old man with synovial chondromatosis of the hip. Both patients came with hip pain, but the former presents at a late stage with osteoarthritis of the hip. The former underwent open arthrotomy debridement to evacuate loose bodies, synovectomy then followed by a total hip replacement. The latter underwent open arthrotomy debridement only to evacuate loose bodies and synovectomy without performing dislocation of the hip. Postoperative outcome was evaluated using plain hip x-ray, pain scale with VAS, and functional score with Harris Hip Score (HHS). Results: At 1-year follow up, both subjects demonstrate an improving functional outcome. The former patient had an improved HHS from 39 to 91 while the latter had an improved HHS from 68 to 93. With complete removal of the metaplastic tissue and synovectomy, the recurrence of the chondromatosis is not apparent yet until now. Discussion: Arthrotomy debridement only or arthrotomy debridement followed by total hip replacement can be considered as an option in treating synovial chondromatosis of the hip as both show a successful outcome. A selective method of treatment must be considered in our decision making for each individual.